Revitalisasi Taman Mini Indonesia Indah Sebagai Icon Wisata Budaya di Jakarta: Revitalization of Taman Mini Indonesia Indah as a Cultural Tourism Icon in Jakarta - Farrah Munif; Puan Maharani Elfauda; latif Bisri (OGZ Research & Publishing, 2025)
This study investigates the revitalization process of Taman Mini Indonesia Indah (TMII) during the 2022–2023 period, examining its impact on the park’s image as a cultural tourism destination and identifying the challenges faced during implementation. Employing a qualitative research design, data were collected through direct observation, semi-structured interviews with management and cultural practitioners, and documentation, and were analyzed using Spradley’s ethnographic model. The results reveal that the “green pillar” of the revitalization was achieved through the creation of motor-vehicle-free zones, the introduction of environmentally friendly transportation systems, and the expansion of green open spaces. These interventions enhanced visitor comfort, cleanliness, and overall attractiveness, while simultaneously revitalizing local traditions and fostering community participation. Moreover, the revitalization generated positive economic effects by creating new employment opportunities and stimulating local business activities.